INNOVATION Study (Impact of Immediate Stent Implantation Versus Deferred Stent Implantation on Infarct Size and Microvascular Perfusion in Patients With ST-Segment–Elevation Myocardial Infarction). (December 2016) - Kim, Je Sang; Lee, Hyun Jong; Woong Yu, Cheol; Kim, Yang Min; Hong, Soon Jun; Park, Jae Hyung; Choi, Rak Kyeong; Choi, Young Jin; Park, Jin Sik; Kim, Tae Hoon; Jang, Ho-Jun; Joo, Hyung Joon; et al.
Abstract : Background—: The aim of this study was to assess whether deferred stenting (DS) reduces infarct size and microvascular obstruction (MVO) compared with immediate stenting (IS) in primary percutaneous coronary intervention for ST-segment–elevation myocardial infarction. Methods and Results—: From February 2013 to August 2015, 114 patients (mean age: 69 years) were randomized into the following 2 groups: DS with an intention to stent 3 to 7 days later or IS after primary reperfusion in 2 centers. The primary and secondary end points were infarct size and the incidence of MVO, respectively, assessed by cardiac magnetic resonance imaging at 30 days after primary reperfusion. The median time to the second procedure in the DS was 72.8 hours. Six patients in the DS group were crossed over to the IS group because of progression of dissection or safety concerns after randomization. In the intention-to-treat analysis, DS did not significantly reduce infarct size (15.0% versus 19.4%; P =0.112) and the incidence of MVO (42.6% versus 57.4%; P =0.196), compared with IS. However, in anterior wall myocardial infarction, infarct size (16.1% versus 22.7%; P =0.017) and the incidence of MVO (43.8% versus 70.3%; P =0.047) were significantly reduced in the DS group. There was no urgent revascularization event during deferral period. Conclusions—: A routine DS did not significantly reduce infarct size and MVO compared with IS, although it was safe. The beneficial effect of DS in patients with anterior myocardial infarction should be confirmed by larger randomized studies. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02324348. Abstract : Supplemental Digital Content is available in the text.